Bloom’s “Daisy Ring” Taxonomy - Notar, Charles E. (Advances in Social Sciences Research Journal, 2025)
Present day illustrations of Bloom’s taxonomy do not give credence to the creation of knowledge. Bloom 1956 starts with knowledge. Bloom 2001 tells us how it is created. However, where is the product … knowledge. A more realistic presentation of Bloom would be a combination of 1956 and 2001. Today we teach performance objectives. The new “Daisy Ring” illustration of Bloom is more in tune with critical thinking, performance objectives, and their assessment and the lifelong learner.